Enhancing EFL writing skills through social media: A mixed-methods study on the impact of YouTube and Instagram short videos in medical English education - Alshraah, Shadi; Hammouri, Dina; Aldaghri, Ashwaq; Althobiti, Mashael (Research Journal in Advanced Humanities, 2025)
This study investigates the extent to which incorporating targeted social media content can enhance the writing proficiency of medical students enrolled in English for Medical Purposes (EMP) courses. By integrating modern digital tools—specifically short videos from platforms such as YouTube and Instagram—into the curriculum, the research seeks to promote more dynamic and effective learning experiences tailored to the complexities of medical English. Employing a mixed-methods approach, the study involved 64 undergraduate participants, divided into an experimental group (EG) and a control group (CG), as well as survey data from 35 university instructors. Initial pretest results confirmed that both groups exhibited similar levels of writing proficiency. However, following the intervention, the EG demonstrated a marked improvement, with a mean score of 79.05 (SD = 3.056), significantly outperforming the CG, which had a mean of 34.46 (SD = 9.355). The high T-value (15.63) and low p-value (0.001) indicate a statistically significant difference between the groups’ post-test performances. These findings suggest that traditional instructional strategies are insufficient for fostering writing development in EMP contexts, while the integration of social media-based content proves highly effective.